Evaluation of Anthelmintic Activities of Persea americana and Musa sikkimensis - Nihar Ranjan Sarmah; Preety Rani Gupta; Raksha Sharma; Tashi Narbu Moktan; Ananya Bhattacharjee (Journal of Pharmaceutical Research, 2024)
The goal was to know about the anthelmintic properties of the leaves of P. americana and peels of M. sikkimensis. An ethanolic extract from the leaves of P. americana and aqueous extract of M. sikkimensis was used to screen for phytochemicals and analyse the anthelmintic activity on Indian earthworm Pheretima posthuma to determine its therapeutic capabilities. The experiment was carried out by preparing standard drug solution (Albendazole), P. americana leaf extract and M. sikkimensis peel extract in a concentration range of 5mg/ml, 10mg/ml and 20mg/ml respectively for each. The earthworms were placed in a beaker with solutions of varying concentrations. The time of paralysis and death was noted and plotted in a graph. From the results, it was found that P. americana and M. sikkimensis extract caused paralysis in less time in a dose-dependent manner, as well as the death was caused much earlier compared to the control group. This suggests that P. americana and M. sikkimensis extract exhibited strong anthelmintic activity. Furthermore, a link has been found between anthelmintic activity and high levels of flavonoids, terpenoids and tannins. Flavonoids, tannins and terpenoids found in various extracts have been proven to have anthelmintic properties in earlier investigations. Persea americana have been reported to have alkaloids, flavonoids, glycosides, saponins, steroids, tannins, proteins, and Musa sikkimensis have been reported to have alkaloids, glycosides, saponins, steroids, terpenoids, tannins, proteins. These results lead to the conclusion that P. americana and M. sikkimensis extract may possess anthelmintic activity. Keywords: Anthelmintic activity, Helminth, Musa, Avocado